A Longitudinal Actor-Partner Interdependence Mediation Model of Storybook Reading: Children's Word Use as a Mediator. (3rd May 2020) - Meng, Christine
ABSTRACT: The present study examined the dyadic nature of fathers' and mothers' reported frequency of storybook reading by testing (1) the longitudinal association in parents' frequency of storybook reading when their children were 10.47 months old and 52.95 months old, (2) the interdependence between both parents' reported frequency of storybook reading, (3) whether children's word use would be a potential mediator, and (4) potential moderators (e.g., education levels, language skills). The analytical sample consisted of 8, 400 two-parent households from the Early Childhood Longitudinal Study-Birth Cohort (ECLS-B). The actor-partner interdependence mediation model was conducted. Findings showed a significant effect for the continuity in mothers' storybook reading, but not fathers. Mothers' reported storybook reading when their children were 10.47 months old significantly predicted fathers' reported storybook reading when their children were 52.95 months old. Children's word use was not a significant mediator. Implications and future research are discussed.